2015
DOI: 10.1007/s11105-015-0871-0
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Relationship and Diversity Analysis of Faba Bean (Vicia Faba L. var. Minor) Genetic Resources Using Morphological and Microsatellite Molecular Markers

Abstract: Assessment of genetic diversity is an essential component in germplasm characterization and utilization. Molecular markers serve as a valuable tool to assess the genetic variation and germplasm identification, which play a key role for faba (Vicia faba L.) bean breeding. In this study, we analyzed the genetic diversity of faba bean accessions based on simple sequence repeats (SSRs) and morphological traits. Forty-six faba bean accessions, originating from different countries and from the ICARDA breeding progra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
22
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(43 citation statements)
references
References 41 publications
4
22
0
Order By: Relevance
“…Indeed, molecular markers are increasingly used for the detection of differences at the DNA level among and within crop populations (Hoxha et al 2004). Although sodium dodecyl sulfate (SDS)-polyacrylamide gel electrophoresis (PAGE) (Hou et al 2015) and molecular markers such as ISSR (SalazarLaureles et al 2015) and SSR have been widely used to assess genetic diversity in faba bean (Alghamdi et al 2012;Suresh et al 2013;Abid et al 2015), the information on the genetic variability and relationship among Tunisian germplasms is limited.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, molecular markers are increasingly used for the detection of differences at the DNA level among and within crop populations (Hoxha et al 2004). Although sodium dodecyl sulfate (SDS)-polyacrylamide gel electrophoresis (PAGE) (Hou et al 2015) and molecular markers such as ISSR (SalazarLaureles et al 2015) and SSR have been widely used to assess genetic diversity in faba bean (Alghamdi et al 2012;Suresh et al 2013;Abid et al 2015), the information on the genetic variability and relationship among Tunisian germplasms is limited.…”
Section: Discussionmentioning
confidence: 99%
“…The evaluation of genetic variability among faba bean landraces using agro-morphological and molecular markers revealed that sequence-related amplified polymorphism (SRAP) and amplified fragment length polymorphism (AFLP) markers are used to determine the genetic variability among genotypes (Ammar et al 2015;Backouchi et al 2015;Abid et al 2015;Rebaa et al 2017;Alemu et al 2018). AFLP markers and combined SRAP are considered to be remarkably beneficial for the evaluation of genetic variability at the molecular level.…”
Section: Introductionmentioning
confidence: 99%
“…They demonstrate high discrimination power (DP), differentiating the faba bean genotypes with high effectiveness and accuracy levels. It has been reported that 17 SSRs and 15 morphological traits could be used to evaluate the genetic variation among faba bean genotypes originating from different countries, and they were included in the International Center for Agricultural Research in the Dry Areas (ICARDA) breeding program (Ammar et al 2015;Abid et al 2015). Significant differences among the genotypes of the 15 morphological descriptors were identified.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, these traits will eventually form the basic classification reference for cultivar screening. Additionally, studying morphological traits of different cultivars would also permit the identification of eminent phenotypes with stable inheritance for genetic functional research (Abid et al, 2015). Based on a study that investigated how flower color was affected by the structure of flower petals, a theoretical basis for safflower formation and origin was sought (He et al, 2010).…”
Section: Introductionmentioning
confidence: 99%